TINGKAT ADOPSI PETANI TERHADAP PENERAPAN TEKNOLOGI USAHATANI PADI SAWAH DIDESA TORIBULU SELATAN KECAMATAN TORIBULU KABUPATEN PARIGI MOUTONG - Ramadhani, Ramadhani; Howara, Dafina; Arfah, Siti Yulianty Chansah (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study was conducted in South Toribulu Village, Toribulu Subdistrict, Parigi Moutong District, to address the previously unknown levels of farmers' adoption of Integrated Crop Management (ICM). The primary objective was to assess the extent to which farmers in this area have adopted ICM practices for paddy rice cultivation. The research was carried out from December 2020 to February 2021, with the study location selected purposively. The sampling method used was a Simple Random Sampling, encompassing 69 farmer groups, each consisting of 25 members, leading to a total population of 1,725 rice farmers. The findings revealed that the adoption level of high-quality seeds was classified as high. In contrast, the adoption levels for components such as superior varieties, planting systems, fertilizer application, alternate irrigation, integrated pest management (IPM), and weeding were classified as moderate, although there were slight variations in scores across these components. The use of organic matter received an average score of 29.59, while the harvest and post-harvest practices scored 35.73, both of which were categorized as low. Overall, the adoption of Integrated Crop Management for paddy rice was classified as moderate in Toribulu Selatan Village, with an average score of 43.21.